Analisis Penurunan Angka Cakupan Imunisasi Dasar Lengkap di Kelurahan Tua Tunu Indah Puskesmas Gerunggang Tahun 2022 - Ayudita Ayudita; Rahmawati Rahmawati; Megawati Megawati (Inovasi Kesehatan Global, 2024)
Immunization is an effective way to prevent the spread of diseases and plays a crucial role in addressing health issues. The purpose of this study is to analyze the decline in complete basic immunization coverage in Tuatunu Village, under the Gerunggang Community Health Center. The research uses a descriptive qualitative approach with a case study design, which clearly describes the phenomena in the community. The instruments used include observation guidelines, interview guidelines, and the researcher themselves, supported by a voice recorder from a mobile phone. The study employs methods such as observation, interviews, and documentation. Primary data sources were obtained through direct interviews and field observations. The research location is the Posyandu in Tuatunu Village, within the working area of the Gerunggang Community Health Center. The results of the study identified several factors contributing to the decline in immunization coverage, including socio-cultural factors, family support, and support from health workers, cadres, and community leaders. There is a need for improved services and communication between health workers and the community/Posyandu participants, as well as health promotion related to parents' understanding of the benefits of immunization.